Compressive Sensing Based Active Imaging System Using Programable Coded Mask and a Photodiode - Sudhabrata Majumder; Sakshi Gupta; Satish Dubey (IEEE Photonics Journal)
There has been significant progress in the field of compressive sensing (CS) and its applications in various fields in recent years. Here, we have developed a CS-based active imaging system that does not require a pixelated array detector but instead uses a transmissive spatial light modulator as a programmable coded mask. Single-pixel cameras (SPCs) have many applications in fields such as terahertz (THz) and infrared (IR) imaging. With an increase in the number of pixels, array detectors can become expensive, especially in the THz and IR regimes. In this article, we have explored the concept of active illumination, which could be helpful in developing SPCs. The article focuses on the development of an active SPC, and the analysis of how coded masks affect the quality of the reconstructed image.